2017
DOI: 10.3174/ajnr.a5207
|View full text |Cite
|
Sign up to set email alerts
|

Pontomesencephalic Atrophy and Postural Instability in Wilson Disease

Abstract: An increase in the MR Parkinsonism index in Wilson disease is mainly due to midbrain atrophy and it correlates with neurologic severity and abnormal postural reflex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Smolinski et al found that patients with neurological manifestations had significantly higher annualized atrophy rates than other patients (Smolinski et al, 2022) and that the volume of all major brain structures correlated with functional and neurological impairment in patients with WD (Smolinski et al, 2019). In line with previous studies which revealed an association between brain atrophy and cognitive functions (Nagai et al, 2008;Liu et al, 2016), Kalita et al found that midbrain atrophy was associated with nervous system severity through 3D BRAVO sequence measurements of the midbrain and the pons (Kalita et al, 2017). Song et al quantified brain morphological abnormalities by whole brain volume and cortical thickness using 3D T1-weighted images (Song et al, 2021).…”
Section: Discussionmentioning
confidence: 81%
“…Smolinski et al found that patients with neurological manifestations had significantly higher annualized atrophy rates than other patients (Smolinski et al, 2022) and that the volume of all major brain structures correlated with functional and neurological impairment in patients with WD (Smolinski et al, 2019). In line with previous studies which revealed an association between brain atrophy and cognitive functions (Nagai et al, 2008;Liu et al, 2016), Kalita et al found that midbrain atrophy was associated with nervous system severity through 3D BRAVO sequence measurements of the midbrain and the pons (Kalita et al, 2017). Song et al quantified brain morphological abnormalities by whole brain volume and cortical thickness using 3D T1-weighted images (Song et al, 2021).…”
Section: Discussionmentioning
confidence: 81%
“…[ 33 ] Interestingly, brain MRI in severe neurological WD and postural instability may show midbrain atrophy. [ 62 ] The extent and load of brain MRI lesions correlates with clinical severity,[ 33 58 ] and diffusion restriction inversely correlates with duration of disease. [ 42 ] Brain MRI lesions may resolve with clinical improvement in WD.…”
Section: Iagnosismentioning
confidence: 99%
“…[ 33 ] Interestingly, brain MRI in severe neurological WD and postural instability may show midbrain atrophy. [ 62 ] The extent and load of brain MRI lesions correlates with clinical severity,[ 33 58 ] and diffusion restriction inversely correlates with duration of disease. [ 42 ] Brain MRI lesions may resolve with clinical improvement in WD.…”
Section: Linical F Eaturesmentioning
confidence: 99%